PEMBERLAKUAN ATURAN PERKAWINAN ADAT DALAM MASYARAKAT ISLAM LEIHETU-AMBON - Soumena, M. Yasin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2012)
This research aimed at describing empirically the criteria of determining partners for life, the ways of carrying out the wedding and wedding ceremonies before. During, and after the marriage oath with all its regulation sets. These were studied stroke the approach of legal anthropology, namely, observing how to events of customary regulation operated in the empirical world, how the community members behave actually. In the behavior what roles call be seen from the various normative which to place in their surrounding.m Nowadays, in the applications of the customary in the Islamic community of Laihitu, the configuration of customary cultural an Islamic values had taken place. As the Islamic values were unified in to the application of customary cultural plastice, then at that time they were considered as customary regulation. In the terminy the partner for life, a young man shall give priority to regulation factor, descendent and should avoid endogamic system. The nature of family relationship followed by the community was patrilineal system. To carry the wedding ceremonies, there were to choices: (1) through marriage in which the husband carried off his wife to another city or place (â€œbalari biniâ€); and (2) through marriage in which a young man proposed to marry a girl to be his wife (â€œkawin minta biniâ€). One of the two ways could be be done on the condition that the responsibility for the rights and obligations, legal guarantee, and legal certainty should be taken into consideration. Before the wedding ceremonies, it was claimed that both sides unite the perception in one family gathering (Bakumpul basudara). This family gatering was a unifying force for friendship and as a team of successfulness in the wedding ceremonies. The regulation that should be obeyed was the execution of contract (Ijab qabul) according to the procedures and the necessity that the bridegroom should obey the usual regulation of the time he met the bride. After the marriage oath, each family should appliciate the service of all persons taking part actively in the ceremonies by making something as standar.